An Unfinished Journey: The Evolution of Crime Measurement in the United States - Patten, Daniel J (2015)
This article traces the history of crime measurement in the United States beginning with the U.S. census in 1790 while exploring several key pieces of history that influenced how crime is measured today. After discussing the origins of the U.S. census and its contributions to measuring crime, the Chicago School of Sociology is observed for its monumental influence on early criminology in America. Next, the division of sociology and criminal justice into two distinct fields had major implications for measuring crime. How crime is measured is often attributed to the ideological differences between these academic fields. Then, the three primary methods of crime measurement used today: (1) the Uniform Crime Reports; (2) self-report surveys; and (3) victimization surveys are given a critical gaze. More importantly, the social, political, and historical influences that led to the adoption of these methods are discussed and their ramifications reviewed. Finally, a mixed method approach based on the history of crime measurement development is suggested for future criminologists and sociologists alike